Instructed Partnership Appreciation in Depression: Effects on Mood, Momentary Relationship Satisfaction, and Psychobiological Arousal - Warth, Marco; Stoffel, Martin; Winter, Friederike; Jarczok, Marc N.; Aguilar-Raab, Corina; Ditzen, Beate (Frontiers in Psychiatry, 2020)
Background: Depressive disorders are associated with attentional bias and social anhedonia. There is evidence supporting the hypothesis that depressed individuals participate less in potentially rewarding social situations and exhibit alterations in stress reactivity. With the present study, we aimed at investigating the affective and psychobiological response of couples with a depressed (female) partner in an instructed partnership appreciation task (PAT) that included positive and appreciative communication. Methods: In a quasi-experimental repeated-measures design, depressive couples (DCs) – i.e., the female partner being diagnosed with a depressive disorder – were compared to non-depressive couples (NDCs). Study outcomes were the PAT-induced changes in state mood, momentary relationship satisfaction, salivary cortisol, and salivary alpha-amylase. Additionally, we assessed psychometric baseline data on depression, relationship quality, social support, and chronic stress. Data was analyzed using multilevel modeling. Results: A total of 184 individuals from N = 47 DCs and N = 45 NDCs were included. DCs were characterized by higher depressiveness, lower relationship quality, less actually received social support from the partner, and higher chronic stress than NDCs. Manipulation checks led to the additional exclusion of two couples. Regarding mood, depressed women showed lower baseline scores and no significant differences in mood increase compared to non-depressed women (p = 0.107), while increases in relationship satisfaction were stronger in the depressed group (p = 0.035). In addition, we found a significantly stronger cortisol increase in depressed women, but only if relationship duration was taken into account as a moderating factor (p = 0.022). No significant group differences were found for women’s amylase trajectories or for sex-dependent interaction effects on the couple level (all p > 0.05). Conclusions: Instructed engagement in positive couple interaction may require high effort and increased psychobiological arousal, but may finally result in emotional and social benefits in depressed women. While these findings encourage speculations about the therapeutic application of PAT-like couple interaction, more research is needed on the effectiveness of such interventions and on the moderating role of relationship duration in depression and couple functioning.